Pogańskie idee polityczne w chrześcijańskim świecie. Władza, jej granice i źródła legitymizacji w ocenie autora dialogu περι πολιτικησ επιστημεσ (De scientia politica) - Wolińska, Teresa (Vox Patrum, 2016)
De scientia politica was written in the form of a Platonist dialogue and constituted a political and philosophical theory of a state and its ruling king or emperor. The writing was created in the 6th century A.D., during the reign of Justinian I. The information about its existence had been known from a short note in Photios Library, long before its parts were found and published in 1827. The author – excellently educated and continuing the Platonist and Neo-Platonist tradition – preferred to remain anonymous, despite some attempts of identification. The work is highly intellectual, addressed to educated readers, capable of understanding sophisticated literary references and allusions. The author’s effort to give it a scholarly character is clearly visible. Book IV was devoted to military affairs, whereas Book V – to imperial power, where the author discussed the problem of its origin, limitations, principles of choosing a ruler and ruler’s obligations. While expressing the principles which a 6th century ruler (i.e. already a Christian ruler) should obey, the author makes references to the Greek and Roman writers – Homer, Plato and Neo-Platonists, Cicero, Seneca, Titus Livius and others. The Persian model was not alien to him either and it is not always clear if he took from the pagan or the Christian heritage. Frequent references to the predecessors’ thought do not mean that the author of De Scientia politica uncritically took over all of their views. He rather selected from the antique heritage what he thought to be current and at the same time he tried to adjust his work to the reality of a 6th century world. The work, albeit preserved only in fragments is, according to P. N. Bell: „the only surviving example of a Neo-Platonic political theory outside the Arab world”.